Приватний і публічний інтерес у системі податкових правовідносин - Кармаліта, Марія Володимирівна (ФОП Стрихар А. М. , м. Хмельницький, вул. Красовського, 2019)
У монографії здійснено системний науково-практичний аналіз правового забезпечення реалізації приватного та публічного інтересу в оподаткуванні. З урахуванням здобутків фінансового права та загальної теорії права запропоновано концептуальні засади правового забезпечення реалізації приватного і публічного інтересу в оподаткуванні та механізм їх збалансування під час нормотворчості та правозастосування. Сформульовано поняття «інтерес в оподаткуванні». Визначено правову природу приватного та публічного інтересу в оподаткуванні. Надано їх характерні прояви у податкових правовідносинах. Окрему увагу приділено принципам податкового права як прояву приватного та публічного інтересу в оподаткуванні. Визначено принцип балансу приватного і публічного інтересу в оподаткуванні як запровадження рівноваги між переслідуваною державою метою (використати максимально свій податковий потенціал як організації публічної влади населення) та створенням умов для справедливого оподаткування, забезпечення гідного життя або функціонування платника податків, реалізації його індивідуальної свободи. Розкрито особливості поєднання під час встановлення та справляння податкових платежів у державі. Акцентовано увагу на податковій безпеці як складовій національної безпеки – стану, за якого відбувається забезпечення реалізації приватного і публічного інтересу в оподаткуванні. Сформовано концептуальні підходи до встановлення балансу приватного і публічного інтересу при вирішенні податкових спорів, вироблено науково обґрунтовані пропозиції щодо удосконалення чинного податкового законодавства на основі порівняльного аналізу здобутків вітчизняної і зарубіжної правової доктрини та юридичної практики.

The systematic scientific and practical analysis of legal support of realization of private and public interest in taxation was carried out in the monographs. Taking into account the results of research in the science of financial law and general theory of law, the concept of legal support for private and public interest in taxation and a mechanism for balancing them in the process of norm-setting and legal implementation was proposed. The concept of «interest in taxation» is formulated, which means the aspiration of participants of tax legal relations to satisfy economic and social needs by formation of necessary financial maintenance at the expense of tax incomes. The legal nature of private and public interest in taxation is determined. Their characteristic features are presented. The public interest in taxation is the law, interest and aspiration of the society, which are ensured by the norms and are manifested in the stable and sufficient receipt of taxes and fees into the budgets in order to direct them to financing the basic public needs and guaranteeing its existence and development. Private interest in taxation is the law, interest and aspiration of the taxpayer, secured by the norms, which arise in the process of performance of his/her tax obligation, and is directed to obtaining tangible or intangible benefits in the field of taxation, satisfaction of conscious needs, etc. Special attention is paid to the principles of tax law as an expression of private and public interest in taxation. The principle of balance of private and public interest in taxation is defined as the introduction of balance between the pursued goal of the state to use the maximum of its tax potential as an organization of public power of the population and creation of conditions for fair taxation, ensuring a decent life or functioning of the taxpayer, the implementation of his/her individual freedom. The peculiarities of the combination in the process of establishment and withdrawal of tax payments by the state are revealed. Emphasis is placed on the tax security of state as a component of national security – a state in which the implementation of private and public interest in taxation is ensured. Conceptual approaches to the balance of private and public interest during the resolution of tax disputes were formulated, scientifically based approaches to the improvement of the current tax legislation based on the comparative analysis of the achievements of the domestic and foreign legal doctrine and legal practice were proposed.
Keywords: правове забезпечення; приватний і публічний інтерес в оподаткуванні; податкова політика; принципи податкового права; податкова безпека; legal support; private and public interest in taxation; tax policy; principles of tax law; tax security